Investigating factors contributing to the occurrence of COVID-19 outbreaks in athletes in a scoping review - Kasama, S.; Sasaka, H.; Endo, E. (Japan Journal of Physical Education, Health and Sport Sciences, 2024)
Purpose: Based on a literature review, this study aimed to identify factors associated with outbreaks among athletes during the coronavirus disease 2019 (COVID-19) pandemic and to consider infection prevention measures for athletes.